Bisphenol A and Bisphenol S Induce Endocrine and Chromosomal Alterations in Brown Trout - Frenzilli, Giada; Martorell-Ribera, Joan; Bernardeschi, Margherita; Scarcelli, Vittoria; Jönsson, Elisabeth; Diano, Nadia; Moggio, Martina; Guidi, Patrizia; Sturve, Joachim; Asker, Noomi (Frontiers in Endocrinology, 2021)
Bisphenol A is a widely used compound found in large amount of consumer products. As concerns have been raised about its toxicological and public health effect, the use of alternatives to bisphenol A are now increasing. Bisphenol S is one of the analogues being used as a replacement for bisphenol A despite the fact that little is known about the effects of bisphenol S on living organisms. In this study, we investigated the potential endocrine and genotoxic effects of bisphenol A and bisphenol S in juvenile brown trout (Salmo trutta). The fish were exposed to the compounds for either 2 weeks or 8 weeks via sustained-release cholesterol implants containing doses of 2 mg/kg fish or 20 mg/kg fish of the substances. The effects on the thyroid hormone levels and the estrogenic disrupting marker vitellogenin were evaluated, along with the genotoxic markers micronucleated cells and erythrocytes nuclear abnormalities. An increase in plasma vitellogenin was observed in fish exposed to the high dose of bisphenol A for 2 weeks. At this experimental time the level of the thyroid hormone triiodothyronine (T3) in plasma was elevated after bisphenol S exposure at the high concentration, and paralleled by an increase of micronucleated cells. Moreover, bisphenol A induced an increase of micronuclei frequency in fish erythrocytes after the exposure at the lowest dose tested. Taken together the results indicate that both bisphenol A and its alternative bisphenol S cause endocrine disrupting and genotoxic effects in brown trout, although suggesting two different mechanisms of damage underlying bisphenol A and bisphenol S activity.